Devil's Peak [videorecording (DVD)] - Jephta, Amy; Orton, Matthew; Pelser, Hilton; Henna, Sisanda; Wyngaard, Tarryn; Miller, Shamilla; Meyer, Deon (BBC, 2024)
Brilliant but disillusioned detective Benny Griessel tracks down a vigilante killer in Cape Town. Broken by his previous cases, he returns to stop the bloodshed.